Leading a Community Engagement Approach for Integral Mission in Central Africa and Southeast Asia - Jason Paltzer (Journal of Scholarly Engagement, 2019)
Community engagement is essential in global health mission organizations in order to effectively integrate physical and spiritual health. I experienced a progression in understanding faith-based community engagement in global health during my time as a health director in central Africa and Southeast Asia. The Facilitator phase of this progression leads to understanding the systems and networks as described by the Social-Ecological Model (SEM) and the Holistic Worldview Analysis (HWVA) model. Together, these can be used to guide church workers, faith-based public health practitioners, and development leaders in taking a holistic approach to improving community health and well-being in a way that learns from my experience and focuses on the Facilitator phase as the most effective. Integral mission understands that the physical and spiritual determinants of health are inseparable but is often challenged by diverse partnerships, community beliefs, and assumptions influencing cross-cultural health initiatives. Together, the SEM and HWVA models support a holistic community engagement strategy for integral mission to take place.